Das línguas e das culturas - Brait, Beth; Pistori, Maria Helena Cruz; Lopes-Dugnani, Bruna; Melo Júnior, Orison Marden Bandeira de (Bakhtiniana. Revista de Estudos do Discurso, 2018)
Apresentação do número 13.3